Technical assessment of the Biomass Integrated Gasification/Gas Turbine Combined Cycle (BIG/GTCC) incorporation in the sugarcane industry - Pedroso, Daniel Travieso [UNESP]; Machin, Einara Blanco [UNESP]; Perez, Nestor Proenza [UNESP]; Braga, Lucia Bollini [UNESP]; Silveira, Jose Luz [UNESP] (Elsevier B.V., 2017)
Biomass Integrated Gasifier/Gas Turbine Combined Cycle (BIG/GTCC) systems in the sugarcane industry, are capable to produce more electricity per unit of biomass consumed than the conventional Condensing Extraction Steam Turbine (CEST) systems. A technical analysis of the introduction of BIG/GTCC technology in the sugarcane industry for electricity and heat generation, using wet sugarcane bagasse as fuel, was conducted. For sugar plants, with large steam requirements, the implementation of the pure BIG/GTCC is not convenient due to the size of the required gas turbine and of the gasification island. The partial BIG/GTCC appear to be better alternative, by the combination of the torrefaction pretreatment and entrained flow gasifier, CHOREN Carbo-V type, permitting a net electricity generation efficiency of 14.7% and the increment of the CEST cogeneration efficiency;, using wet sugarcane bagasse as feedstock. This arrangement avoid Observed problems in previous experiences with the continuum handling and feeding of shredded sugarcane bagasse to the gasifier. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Sugar cane bagasse gasification; Entrained flow gasifier; Bagasse torrefaction; Electricity generation